Sciatic nerve injury caused by pre-operative intraneural injection of local anaesthetic during total hip replacement. - Uppal, H; Gwilym, S; Crawfurd, E; Birch, R (2007)
We report a case of iatrogenic sciatic nerve injury caused by pre-operative intraneural injection of local anaesthetic at total hip replacement. To our knowledge, this is unreported in the orthopaedic literature. We consider sacral nerve blockade in patients undergoing total hip replacement to be undesirable and present guidelines for the management of peri-operative sciatic nerve injury.